A Synergistic Nephroprotective Activity of A Miracle Drink Ayurvedic Proprietary Medicine Renal Support A Novel Therapy for Chronic Kidney Disease in Human - S. M. Raju (International Journal of Ayurveda and Pharma Research, 2022)
Miracle drink “Renal Support (S-5)” an Ayurvedic formulation in conjugation with other cardiovascular support (S3), Sugar Care (S10), and liver health support (S4) was scientifically evaluated on 12 humans subjects for its therapeutic potential in treating chronic kidney diseases caused due to: a) Induce of pain killers medication, and other medications, b) Chronic diabetes, c) Blood pressure. Patients suffering from renal failure due to over medications, pain killer medication and BP were advised to take 15ml of Renal Support and S3 twice a day morning and evening before food, and 15ml of S4 trice a day. As the main biomarker of kidney disease, creatinine was monitored every month till three months of treatment whereas; blood urea and hemoglobin were screened at month end. Cytotoxicity and nephroprotective activity of Renal Support were evaluated on Baby Hamster Kidney Fibroblast cells (BHK-21). Radical decline in serum creatinine content was observed from 6.31mg/dl to 1.80mg/dl (68%), 1.20mg/dl (79%), and 0.84mg/dl (82%) on 30, 60, and 90 days of treatment respectively and in 90 days of treatment most of the patients showed 50 to 83% creatinine reduction. A significant decrease in the blood urea from 91mg/dl to 30mg/dl(67%) and hemoglobin content from 7.27 to 11.77g% was observed in 30days of treatment and the majority of patients showed >50% of blood urea reduction. No toxicity of Renal Support towards BHK-21 was noticed and showed 40.92% and 47.54% nephroprotective activity. A novel, natural-based, and safe Ayurveda formulation with significant nephroprotective potential for CKD treatment was proposed in the present study.